Pneumoperitoneum Pada Pasien Covid-19: Laporan Kasus - Hidayat, Imam; Latief, Shofiyah; Bulkis, Bulkis (Universitas Pahlawan Tuanku Tambusai, 2025)
Background: Pneumoperitoneum is a serious medical condition characterized by the presence of air or gas in the peritoneal cavity. This phenomenon often requires immediate surgical intervention, although some cases can be non-surgical. In the context of COVID-19, pneumoperitoneum may emerge as an unusual complication that requires in-depth understanding of its mechanisms for appropriate management. Case Presentation: The case of a 63-year-old man with COVID-19 and spontaneous pneumoperitoneum without evidence of visceral perforation is reported. Patients underwent radiological examinations including X-ray and CT scan for diagnosis and monitoring, while management was carried out conservatively without surgical intervention. The examination revealed pneumoperitoneum with signs of Macklin effect without evidence of organ perforation. The patient was maintained with oxygen via nasal cannula, and recovery was marked by resorption of the pneumoperitoneum and clinical improvement within seven days. No further complications were found, and the patient was successfully removed.Conclusion: Pneumoperitoneum in COVID-19 patients can occur without organ perforation, known as non-surgical spontaneous pneumoperitoneum. Mechanisms involving the Macklin effect and high oxygen pressure are the main factors. Conservative management can be a safe and effective approach in cases without surgical indications. Further studies are needed to understand these complications in depth, especially in relation to COVID-19.